New ages from Boomplaas Cave, South Africa, provide increased resolution on late/terminal Pleistocene human behavioural variability. Issue 2 (3rd April 2018) - Pargeter, Justin; Loftus, Emma; Mackay, Alex; Mitchell, Peter; Stewart, Brian
ABSTRACT: Boomplaas Cave, South Africa, contains a rich archaeological record, with evidence of human occupation from >66, 000 years ago until the protohistoric period. Notwithstanding a long history of research at the site, its existing chronology can benefit from revision. Many of the site's members are currently delimited by only a single conventional radiocarbon date and some of the existing dates were measured on materials now known to be unsuitable for radiocarbon dating. Here we present the results of an ongoing effort to redate key late/terminal Pleistocene sequences in southern Africa. This paper presents a Bayesian-modelled radiocarbon chronology for the late/terminal Pleistocene horizons at Boomplaas. Our model incorporates previously published radiocarbon dates as well as new accelerator mass spectrometry ages. We also present archaeological evidence to examine in greater detail than was previously possible the nature of occupation patterning across the late/terminal Pleistocene and to assess technological change across two of the site's Last Glacial Maximum (LGM) members. The new dates and archaeological data confirm that the site was occupied in a series of low intensity events in the early LGM and immediately thereafter. The site was occupied intensively in the terminal Pleistocene in line with major changes in palaeoenvironments and sea-level fluctuations. The lithic data show the use of variable technological strategies in contexts of shifting mobility and site occupation patterns. Our discussion informs upon hunter-gatherer behavioural variability that did not, and should not be expected to, reflect the strategies adopted and adapted by a handful of well-known arid-zone hunter-gatherers in the twentieth-century Kalahari.